2011
DOI: 10.1038/ncomms1427
|View full text |Cite
|
Sign up to set email alerts
|

Iron-based cathode catalyst with enhanced power density in polymer electrolyte membrane fuel cells

Abstract: H(2)-air polymer-electrolyte-membrane fuel cells are electrochemical power generators with potential vehicle propulsion applications. To help reduce their cost and encourage widespread use, research has focused on replacing the expensive Pt-based electrocatalysts in polymer-electrolyte-membrane fuel cells with a lower-cost alternative. Fe-based cathode catalysts are promising contenders, but their power density has been low compared with Pt-based cathodes, largely due to poor mass-transport properties. Here we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

31
1,203
3
9

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 1,381 publications
(1,263 citation statements)
references
References 51 publications
31
1,203
3
9
Order By: Relevance
“…In a search for high‐performance alternative NPMCs to Pt cathode over the last decade, significant progress has been made from new catalyst synthesis 6, 7, 8, 9, 10. Among the studied formulations, iron‐nitrogen‐carbon (Fe‐N‐C) catalysts are the most promising in terms of their activity and stability in more challenging acidic electrolytes 11, 12, 13, 14, 15.…”
Section: Introductionmentioning
confidence: 99%
“…In a search for high‐performance alternative NPMCs to Pt cathode over the last decade, significant progress has been made from new catalyst synthesis 6, 7, 8, 9, 10. Among the studied formulations, iron‐nitrogen‐carbon (Fe‐N‐C) catalysts are the most promising in terms of their activity and stability in more challenging acidic electrolytes 11, 12, 13, 14, 15.…”
Section: Introductionmentioning
confidence: 99%
“…We also demonstrated that FeN x C y moieties and Fe@N‐C species are moderately active toward PRR, proving their possible roles in both direct (major path) and indirect 4 e − ORR pathways. Since the synthesis of Fe‐N‐C catalysts with only FeN x C y moieties,10b, 15 only Fe@N‐C particles,10a or their combination3b,3d, 17 is now controllable, the understanding of the nature of active sites for PRR provided herein offers new insights for the rational design of advanced Fe‐N‐C catalysts with high selectivity and expectedly improved durability in polymer electrolyte fuel cells. …”
mentioning
confidence: 99%
“…Polymer electrolyte membrane fuel cell (PEMFC) offers much higher fuel efficiency and lower point‐of‐use emission over the combustion engine 1. These advantages, in addition to longer operating time and fast refueling, render it more competitive than the conventional battery devices.…”
mentioning
confidence: 99%
“…These advantages, in addition to longer operating time and fast refueling, render it more competitive than the conventional battery devices. PEMFC has indeed drawn a growing market share in light duty vehicle, bus and material handling vehicle propulsion as well as in back‐up and remote power systems 1. The efficiency and performance of the widely used low temperature version of this device, however, is limited by the oxygen (O 2 ) reduction reaction (ORR) at or near ambient temperature on its cathode side 2.…”
mentioning
confidence: 99%